Establishment of Chemically Induced Arthritis and Diabetes Combinedly in Wistar Rats: An Experimental Study - Negi, Usha; Chhibber, Sanjay; Kumari, Seema (International Journal of Scientific Research in Biological Sciences, 2019)
The purpose of the present study was to establish combined animal model of chemically induced rheumatoid arthritis and diabetes and study various parameters. The study was conducted on adult male Wistar rats. Arthritis was induced by injecting CFA (Freund`s complete adjuvant) followed by administration of Alloxan monohydrate intra-peritoneally. The levels of TNF-α, IL-1β, IL-6, and IL-10 in sera were measured using ELISA. Histopathological changes in joint tissues, kidney and pancreas were examined using haematoxylin and eosin (H&E). Swelling and inflammation occurred within 24 hr with a significant increase in paw volume which showed no resolution till the 30th day. There was significant increase in blood glucose levels. Bodyweight, GSH and IL-10 levels were decreased in serum of diseased group animals. Spleen & thymus index, nitric oxide, MDA, MPO, GSH, and serum triglyceride levels were elevated in diseased animals. Also, pro-inflammatory cytokine levels were extremely high in diseased animals as compared to control group. The joint histology showed synovial hyperplasia and inflammatory cell infiltration in joint tissues. The pancreas histology results showed disruption and reduction in the size of Islet of Langerhans. Radiological analysis showed deformation in bones. All these parameters confirmed the successful establishment of combined animal model for diabetes and arthritis.